Determinate primary root growth as an adaptation to aridity in Cactaceae: towards evolution and genetic control of the trait - Shishkova, Svetlana (2013)
Background and Aims Species of Cactaceae are well adapted to arid habitats. Determinate growth of the primary root, which involves early and complete root apical meristem (RAM) exhaustion and differentiation of cells at the root tip, has been reported for some Cactoideae species as a root adaptation to aridity. In this study, the primary root growth patterns of Cactaceae taxa from diverse habitats are classified as being determinate or indeterminate, and the molecular mechanisms underlying RAM maintenance in Cactaceae are explored. Genes that were induced in the primary root of Stenocereus gummosus before RAM exhaustion are identified. Methods Primary root growth was analysed in Cactaceae seedlings cultivated in vertically oriented Petri dishes. Differentially expressed transcripts were identified after reverse northern blots of clones from a suppression subtractive hybridization cDNA library. Key Results All species analysed from six tribes of the Cactoideae subfamily that inhabit arid and semi-arid regions exhibited determinate primary root growth. However, species from the Hylocereeae tribe, which inhabit mesic regions, exhibited mostly indeterminate primary root growth. Preliminary results suggest that seedlings of members of the Opuntioideae subfamily have mostly determinate primary root growth, whereas those of the Maihuenioideae and Pereskioideae subfamilies have mostly indeterminate primary root growth. Seven selected transcripts encoding homologues of heat stress transcription factor B4, histone deacetylase, fibrillarin, phosphoethanolamine methyltransferase, cytochrome P450 and gibberellin-regulated protein were upregulated in S. gummosus root tips during the initial growth phase. Conclusions Primary root growth in Cactoideae species matches their environment. The data imply that determinate growth of the primary root became fixed after separation of the Cactiodeae/Opuntioideae and Maihuenioideae/Pereskioideae lineages, and that the genetic regulation of RAM maintenance and its loss in Cactaceae is orchestrated by genes involved in the regulation of gene expression, signalling, and redox and hormonal responses.